The Effect Of Consumption Of Soy Milk And Tempeh In Women Aged 20-30 Years With Premenstrual Syndrome - Fillah fithra dieny; Azizah Dynda Dwiputri; Aryu Candra (Window of Health : Jurnal Kesehatan, 2025)
There are 73.3% of women in Bekasi experiencing symptoms of premenstrual syndrome (PMS). Isoflavone can help with PMS symptoms. The aglycone form of isoflavones has high bioavailability. Analyze the consumption of tempeh and soy milk in reducing SPAF (Shortened Premenstrual Assessment Form) scores. The study used a quasi-experimental method with a pretest and posttest control group design. The intervention was giving soy milk and tempeh for 14 days before menstruation. The sampling technique was used purposive sampling as many as 30 women and divided into 3 groups. PMS symptom assessment using the SPAF questionnaire. The dependent variable in this study is PMS. The independent variables in this study were the consumption of soy milk and tempeh. And the cofounded variables in the study are physical activity, food intake, and stress factors. Data analysis will be carried out using paired t-tests, One-Way ANOVA, and ANCOVA. Consuming soy milk in the treatment group can reduce the SPAF score (p = 0.003). Meanwhile, there was no significant decrease in the group that consumed tempeh (p = 0.105). There was no significant difference in symptom reduction between tempeh and soy milk groups (p = 0.818). The influence of confounding variables (R = 0.560), namely physical activity (p = 0.042). Consumption of soy milk can significantly reduce SPAF scores, while the decrease in SPAF score on tempeh consumption is not significant. It is noted that there is another strong influence, namely high physical activity.